2008
DOI: 10.1007/s00412-008-0179-z
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of 35S and 5S rRNA genes in Artemisia (family Asteraceae): first evidence from angiosperms

Abstract: Typically in plants, the 5S and 35S ribosomal DNA (rDNA) encoding two major ribosomal RNA species occur at separate loci. However, in some algae, bryophytes and ferns, they are at the same locus (linked arranged). Southern blot hybridisation, polymerase chain reactions (PCR), fluorescent in situ hybridisation, cloning and sequencing were used to reveal 5S and 35S rDNA genomic organisation in Artemisia. We observed thousands of rDNA units at two-three loci containing 5S rDNA in an inverted orientation within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 60 publications
2
68
0
Order By: Relevance
“…In relation to Southern blot analyses, García et al [2009] indicated that a ladder of fragments is expected in species with tandem arrays of 5S rDNA since in most angiosperms these genes contain a single conserved Bam HI site [Röser et al, 2001]. A similar outcome was observed in Citrus medica (used here as an outgroup).…”
Section: Linkage Of 5s and 45s Rdna Sequencesmentioning
confidence: 52%
See 2 more Smart Citations
“…In relation to Southern blot analyses, García et al [2009] indicated that a ladder of fragments is expected in species with tandem arrays of 5S rDNA since in most angiosperms these genes contain a single conserved Bam HI site [Röser et al, 2001]. A similar outcome was observed in Citrus medica (used here as an outgroup).…”
Section: Linkage Of 5s and 45s Rdna Sequencesmentioning
confidence: 52%
“…The most common situation found in higher plants is that both the 5S and 18S-5.8S-25S rDNA sequences are organized separately in tandem arrays distributed in one or more loci per genome [Srivastava and Schlessinger, 1991]. However, exceptions to this rule have been reported for several unicellular eukaryotes [Drouin and Moniz de Sá, 1995], bryophytes [Sone et al, 1999] and more recently in Artemisia (Asteraceae) [García et al, 2009]. Our FISH analyses in three species of Achyrocline have shown that there is only one 5S and one 45S rDNA site in these species and that both co-localize in the pericentromeric region of chromosome pair 10.…”
Section: Linkage Of 5s and 45s Rdna Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…The 45S-5S unit arrangements were not considered to be present in seed plants until recently, when García et al (2009García et al ( , 2010 detected this type of linkage in a wide sample of taxa belonging to the phylogenetically advanced Asteraceae family. Our finding that the 45S-5S loci are linked in Ginkgo suggests a colocalization of the two nuclear ribosomal gene families in the early evolutionary history of seed plants, indicating that a reassessment of the organization and molecular evolution of rDNA genes of basal plants is still necessary, as the results of Wicke et al (2011) should be viewed with great caution.…”
Section: Early Evolutionary Colocalization Of the 45s And 5s Gene Fammentioning
confidence: 99%
“…Recently, however, it has been unequivocally shown for the first time, using molecular cytogenetics, Southern blot hybridization, PCR-based techniques and DNA sequencing, that 5S genes can be embedded within the 45S multigene family in angiosperms (Asteraceae; García et al, 2009;García et al, 2010). The detailed survey within Asteraceae has revealed that in about 25% of the species in this family, the two ribosomal gene families have been combined into a single, linked 45S-5S unit (García et al, 2010).…”
Section: Introductionmentioning
confidence: 99%